A brief measure of narcissism among female juvenile delinquents and community youths: The Narcissistic Personality Inventory–13 - Pechorro, Pedro Fernandes Santos (2018)
Research on narcissism has a long tradition, but there is limited knowledge regarding its application among female youth, especially for forensic samples of incarcerated female youth. Drawing on 377 female adolescents (103 selected from forensic settings and 274 selected from school settings) from Portugal, the current study is the first to examine simultaneously the psychometric properties of a brief version of the Narcissistic Personality Inventory (NPI-13) among females drawn from incarcerated and community settings. The results support the three-factor structure model of narcissism after the removal of one item due to its low factor loading. Internal consistency, convergent validity, and discriminant validity showed promising results. In terms of criterion-related validity, significant associations were found with criterion-related variables such as age of criminal onset, conduct disorder, crime severity, violent crimes, and alcohol and drug use. The findings provide support for use of the NPI-13 among female juveniles.